Carbon Credit - An Eco Friendly Business - Saravan, M. (Prabandhan: Indian Journal of Management, 2011)
Studies on climate change have underscored two points. First that atmospheric commons, namely the Earth's carbon absorbing capacity, is finite and depletable and that growth of emissions due to industrialization poses a threat to mankind. Secondly, it has been established that per capita emission is strongly correlated with economic prosperity. It is also recognized that without providing access to appropriate alternative technology options, developing countries would not be able to pursue their socio-economic goals.